THE PORTRAYAL OF PRE-SERVICE TEACHERS IN IMPLEMENTING A GENRE-BASED APPROACH TO TEACHING WRITING:A CaseStudy ina Junior High Schoolin Bandung - NURYMA, Eka (2012)
This study attempted to portray the implementation of Genre-Based Approach to teaching writing conducted by two pre-service teachers. The framework was taken since some previous studies showed an unsatisfyingresult of its application (see Derewianka, 2003; Astaman; 2010). This study aimed to reveal the understanding that the pre-service teachers had about the approach and how they interpreted it into practical level. The study used qualitative study design (Fraenkel&Wallen, 1990), specifically case study framework (Creswell, 1998; Gall et.al., 2003) since the study tried to describe a phenomenon in its nature. Two pre-service teachers were voluntarily observed when they took the teaching-training program in a junior high school in Bandung. Questionnaire, classroom observation, document analysis and interview were deployed in uncovering the data needed. The result of the study indicated that the pre-service teachers had low understanding about the theory of Genre-Based Approach and this resulted in a problematic teaching process.